(untitled) (International Journal of Engineering and Computer Science, 2014)
Data hiding techniques have an important role with the rapid growth of intensive transfer of multimedia content and private communications. Steganography is the art of hiding information in different ways that prevent detection by unintended user. The Steganography used to transfer data and information from one source to other source through public channel in hidden way. Steganography hides the existence of message so that the information is transferred in stealthful way. Steganography means hiding a message (the embedded message) within a larger one (source cover file) in such a way that an observer cannot detect the presence of the hidden message. Many different carrier files can be used, like digital images which are the most popular on Internet. For hiding secret information in images, there exists a large variety of Steganography techniques some of which are simple and some are more complex than others and all of them have strong and weak features. Various applications have different requirements of the Steganography technique used. This paper intends to give an overview of image Steganography, its uses and techniques. It also attempts to identify the requirements of a good Steganography algorithm and briefly reflects on which Steganography techniques are more suitable for which applications.